The effects of the menstrual cycle on muscle activation patterns and fuel utilization in cold exposure - Maneshi, Anali (University of Ottawa (Canada), 2009)
Cold-induced shivering is characterized by two distinct muscle contraction patterns: continuous low-intensity shivering [at ∼1 to 5% of maximal voluntary contraction (MVC)] and bursts of high-intensity shivering (at 10 to 35% MVC) (Meigal, 2002, Haman et al., 2004). In this context, Haman et al. (2004) showed that carbohydrate (CHO) oxidation rate is directly related to burst shivering rate which increases the proportional recruitment of glycolitic type II fibers. Because most of these studies have been carried out in men, little is still know on the effects of hormonal fluctuations during the menstrual cycle on the dual shivering pattern and energy metabolism in women. Therefore, the purpose of this study was to quantify differences in muscle recruitment pattern and fuel selection in two phases of the menstrual cycle. Muscle recruitment in eight muscles and whole body fuel selection were monitored in women exposed to 120 min of cold exposure (5°C liquid-perfusion suit) during FP and LP. Results show that there is no difference in the onset of shivering, shivering intensity, burst duration and burst shivering rate between LP and FP during steady state shivering (in last 15 min). Similarly, during steady state shivering (T=105-120 min), absolute rates and relative contributions of metabolic fuels to total heat production did not differ between FP and LP. We conclude that hormonal fluctuations during the menstrual cycle do not affect muscle recruitment patterns or substrate utilization in the cold. Whether this important difference in fuel selection modifies muscle shivering activity and/or confers a survival advantage remains to be established.
Keywords: Health Sciences, Recreation.; Biology, Physiology.